Internet of Things (IoT)-based Solution for Real-time Monitoring System in High Jump Sport - Roslan, Muhammad Faris (International Journal of Integrated Engineering, 2019)
Samsung, Fitbit and Sony are advanced companies that have produced various wearable devices for years especially for sports technology for the needs of athletes. The high-tech developments within the Internet of things (IoTs) also have given athletes and coaches a smart way to develop the way the athlete training and play that give us economic benefit. However, recent year the high jump sport monitoring system still used high-speed camera which is non-economical to the athlete and coaches. Besides, the camera itself need technical expertise to setup the devices and the results is hard to understand and not in real-time. Therefore, the aims of this paper is to develop IoT-based solution for real-time monitoring system in high jump sport. Hence, the OpenHAB mobile application (app) was created to communicate between wearable device and server. This mobile app helps athlete to monitor their performances in the smartphone through IoT-based solution rather than using costly gears similar to high-speed camera. The outcomes achieved have revealed promising results since all data can be visualised and monitored in real-time, history of the training can be retrieved via the logs files and the benchmark data acts as a guide to the intermediate athlete to improve the performance.